Focal Xanthogranulomatous Pyelonephritis with Pulmonary Lesions on the Background of Type Two Diabetes Mellitus - Ahmad Enshaei; Arash A. Boora; Diana Taheri; Zahra Changizi; Nahid Bahmani (Case Reports in Radiology)
Focal Xanthogranulomatous pyelonephritis is a rare chronic inflammatory condition of kidneys which usually is associated with postrenal obstruction or renal stone leading to chronic bacterial infection and eventually chronic glomerular inflammation. About 90% of cases are of the diffuse type and associated with staghorn renal calculi. The case presented in this paper is of the focal type in a 58-year-old diabetic female. Interestingly she did not have symptoms or laboratory presentation of chronic renal bacterial infection except for elevated ESR. She sought medical attention due to severe pulmonary infection of the background of morbid obesity. Imaging studies revealed several pulmonary lesions and a large mass of the right kidney which was indistinguishable from renal malignancy. After surgical resection of the right kidney, the lesion is pathologically diagnosed to be a focal Xanthogranulomatous pyelonephritis. The pulmonary lesions were spontaneously resolved about three months following right nephrectomy.